Modification of creep and low cycle fatigue behaviour induced by welding (Fracture and Structural Integrity, 2014)
In this work, the mechanical properties of Waspaloy superalloy have been evaluated in case of welded repaired material and compared to base material. Test program considered flat specimens on base and TIG welded material subjected to static, low-cycle fatigue and creep test at different temperatures. Results of uniaxial tensile tests showed that the presence of welded material in the gage length specimen does not have a relevant influence on yield strength and UTS. However, elongation at failure of TIG material was reduced with respect to the base material. Moreover, low-cycle fatigue properties have been determined carrying out tests at different temperature (room temperature RT and 538°C) in both base and TIG welded material. Welded material showed an increase of the data scatter and lower fatigue strength, which was anyway not excessive in comparison with base material. During test, all the hysteresis cycles were recorded in order to evaluate the trend of elastic modulus and hysteresis area against the number of cycles. A clear correlation between hysteresis and fatigue life was found. Finally, creep test carried out on a limited number of specimens allowed establishing some changes about the creep rate and time to failure of base and welded material. TIG welded specimen showed a lower time to reach a fixed strain or failure when a low stress level is applied. In all cases, creep behaviour of welded material is characterized by the absence of the tertiary creep.
Keywords: Low-cycle fatigue